MASKER WAJAH TRADISIONAL SUMBAWA: KARAKTERISTIK FISIK DAN KIMIA PEEL OFF LOTO MOTONG - Arsally Saskiarty Ndoen; Ariskanopitasari (Faculty of Agriculture Science & Technology, 2023)
The skin is the outmost layer of human body which protect the body from microorganisms, UV light, and other chemicals. The healthiness of the skin can be maintained by the application of skin care product. Sumbawanese have been applying loto motong as a traditional skin care product for its hydrating agent and protecting the skin against UV light. This study aimed to add new alternative to the application of loto motong by Sumbawanese as a peel off mask to preserve local wisdom. This study measured the particle size, homogeneity, spreadability, stickiness, moisture content, pH, and vitamin E content of the loto motong peel off mask. This study shows that the mask formulation was homogenous, has 0.25 mm, 5.30 cm, 6.81 seconds, 9.33%, 6, and 53.89 ppm of particle size, spreadability, stickiness, moisture content, pH, and vitamin E, respectively. The parameter measured complies with the Indonesian National Standard (SNI 164399–1996) which means this peel off mask can be safely used and potentially become the alternative method for loto motong application.